Analisis Kelayakan Bisnis pada Tuju Coffe & Eatery di Kota Bandung - Pitria, Rina; Kamila, Siti Syakira Hasna; Sawalni, Sawalni; Ramadani, Novi; Khairan, Rasyad; Januariansyah, Rifqi; Al Bukhari, Arrizan Fadilah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the business feasibility of Tuju Coffee & Eatery from financial and non-financial aspects. The research method used is a descriptive qualitative and quantitative approach with data collection techniques through interviews, observations, an literature studies. The financial aspect analysis was conducted using the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Benefit Cost Ratio (B/C), and Break Even Point (BEP) method, as well as sensitivity analysis to assess the business’s resilience to changes in key variables. The analysis results show that the NPV value is positive, the IRR is greater than the discount rate used, the Payback Period is relatively short, the B/C value is greater than one, and the Break Even Point can be reached quickly. The sensitivity analysis shows that the business remains viable even if there are changes in revenue and operating costs within reasonable limits. From a non-financial perspective, the strategic location of the business, clear target market, and structured operational management also support the viability of the business. Based on these analysis results, it can be concluded that Tuju Coffee & Eatery is viable to operate and develop.